Strategi Peningkatan Keterlibatan Pegawai Dengan Model 10 C’s “Employee Engagement” Di Baznas Provinsi Jawa Barat - Nadya Adjizah Saeysar; Septhiana Dwiputrianti; Sait Abdullah (Jurnal Ilmiah Global Education, 2026)
This study aims to analyze employee engagement and formulate strategies to enhance employee involvement at the West Java Provincial Board of the National Amil Zakat Agency (BAZNAS) using the 10 C’s Model of Employee Engagement proposed by Seijts and Crim (2006). The research is motivated by the phenomenon in which employee engagement scores at BAZNAS West Java have increased over the past three years; however, this improvement has not been followed by a decrease in employee turnover or an optimal increase in organizational performance. This indicates a potential gap between the measured engagement and the deeper psychological and operational engagement experienced by employees. A qualitative descriptive-analytical approach was employed in this study. Data were collected through in-depth interviews, direct observation, and documentation review involving leaders, division heads, human resource staff, and operational employees. Data analysis was conducted through data reduction, data display, and conclusion drawing. The 10 C’s Model was used as the analytical framework to assess employee engagement across ten dimensions: connect, career, clarity, convey, congratulate, contribute, control, collaborate, credibility, and confidence. The findings reveal that several dimensions have been implemented effectively, particularly connect, collaborate, contribute, and credibility, which reflect strong interpersonal relations, teamwork, and employees’ moral commitment to the institution’s mission. However, several dimensions require further improvement, including career, convey, clarity, and control. Employees expressed the need for clearer career development pathways, more transparent and structured communication, more explicit role definitions, and greater autonomy in decision-making related to their tasks. Additionally, there is a need to strengthen recognition systems, performance management, and policy consistency to enhance employees’ overall work experience. Based on these findings, this study proposes several strategies to improve employee engagement, including: (1) strengthening career development systems and talent management; (2) optimizing internal communication to be more transparent and two-way; (3) enhancing role clarity, SOPs, and performance indicators; (4) expanding employee autonomy and participation in decision- making; (5) strengthening fair and standardized reward systems; and (6) reinforcing collaborative culture and organizational values. These strategies are expected to enhance the quality of employee work experience, reduce turnover, and support the improvement of organizational performance at BAZNAS West Java in a more sustainable manner.